2019
DOI: 10.1371/journal.pone.0216140
|View full text |Cite
|
Sign up to set email alerts
|

Predatory efficacy of five locally available copepods on Aedes larvae under laboratory settings: An approach towards bio-control of dengue in Sri Lanka

Abstract: Many countries are in search of more effective and sustainable methods for controlling dengue vectors, due to undeniable inefficiencies in chemical and mechanical vector control methods. Bio-control of vectors by copepods is an ideal method of using interactions in the natural ecosystem for vector management, with minimum consequences on the environment. Current study determined the predatory efficacy of five locally abundant copepod species on, Aedes larvae under laboratory conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…Besides, Udayanga et al [ 46 ] found that the predatory efficiencies varied significantly among the copepod species; Mesocyclops leuckarti showed the highest predatory efficiency for Ae . aegypti and Ae .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Udayanga et al [ 46 ] found that the predatory efficiencies varied significantly among the copepod species; Mesocyclops leuckarti showed the highest predatory efficiency for Ae . aegypti and Ae .…”
Section: Resultsmentioning
confidence: 99%
“…aegypti and Ae . albopictus larvae [ 46 ]. Mesocyclops aspericornis was the most effective predator of Aedes mosquitoes while Mesocyclops darwini was less efficient [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several such species of copepods, namely, Cyclops vernalis, Megacyclops formosanus, Mesocyclops aspericornis, M. edax, M. guangxiensis, M. longisetus, and M. thermocyclopoides, were reported as active predators of young mosquito instars [40,41]. Udayanga et al [42] reported that Mesocyclops leuckarti had a successful predatory effect on Ae. aegypti and Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental vector control methods include the introduction of biological agents such as larvivorous fish [ 111 ], copepods (a group of small crustaceans) [ 112 ] or Bacillus thuringiensis [ 113 ], typically for larvae control. A study investigating the community effectiveness and efficacy of the use of larvivorous fish for dengue vector control reported that although the use of larvivorous fish could be effective in reducing the immature vector stages in small settings such as containers, these results could be minimal as it would require large coverage of multiple production of larvivorous fish containers to achieve any impact in an area of dengue endemicity [ 111 ].…”
Section: Vector Control Methods For Aedes -Bornmentioning
confidence: 99%